Long‐term tolerability, immunogenicity and efficacy of Nuwiq® (human‐cl rhFVIII) in children with severe haemophilia A. Issue 4 (26th March 2018) - Klukowska, A.; Szczepański, T.; Vdovin, V.; Knaub, S.; Bichler, J.; Jansen, M.; Dzhunova, I.; Liesner, R. J.
Abstract : Introduction: Nuwiq ® (human‐cl rhFVIII, simoctocog alfa) is a 4th generation recombinant human FVIII, without chemical modification or fusion with any other protein, produced in a human cell line. Aim/Methods: This study (GENA‐13) was an extension of the GENA‐03 study in which previously treated children aged 2‐12 years with severe haemophilia A received Nuwiq ® prophylaxis for ≥6 months. GENA‐13 examined long‐term tolerability, immunogenicity and efficacy of Nuwiq ® prophylaxis in children. Results: Of 59 patients enrolled in GENA‐03, 49 continued Nuwiq ® prophylaxis in GENA‐13 for a median (range) of 30.0 (9.5‐52.0) months. No patient withdrew due to drug‐related adverse events or developed inhibitors. Only 2 of 20 518 infusions were associated with possibly related adverse events (dyspnoea, fever). The estimated annualized bleeding rate (ABR) was 0.67 (95% CI: 0.44, 1.02) for spontaneous and 2.88 (95% CI: 1.86, 4.46) for all bleeds. Younger children (2‐5 years) had lower ABRs than children aged 6‐12 years. Annualized bleeding rates were reduced in GENA‐13 vs GENA‐03, especially for spontaneous bleeds in younger children (71% reduction; ABR ratio 0.29 [95% CI: 0.11, 0.74]). Nuwiq ® efficacy was rated as excellent/good in the treatment of 83.0% of 305 evaluated breakthrough bleeds. Surgical prophylaxis with Nuwiq ® was rated as excellent for all 17 assessed procedures. Conclusion: Long‐term treatment with Nuwiq ® for the prevention of bleeds in children with severe haemophilia A was well tolerated, effective and reduced spontaneous bleeding by up to 70% compared with GENA‐03.